How Smart is the Grid? - Lo Cascio, Ermanno; Girardin, Luc; Ma, Zhenjun; Maréchal, François (Frontiers in Energy Research, 2021)
Ancient Romans called 'urbs' the set of buildings and infrastructures, and 'civitas' the Roman citizens. Today instead, while the society is surfing the digital tsunami, 'urbs' and 'civitas' tend to become much closer, almost merging, that we might attempt to condensate these into a single concept: 'smart grid'. Internet of things, artificial intelligence, blockchain, quantum cryptography is only a few of the technologies that are likely to contribute to determining the final portrait of the future smart grid. However, to understand the effective sustainability of complex grids, specific tools are required. To this end, in this article, a new taxonomic framework has been developed starting from a general analysis of the emerging solutions, identifying intersectoral synergies and limitations with respect to the `smart grid' concept. Finally, from the scenario portrayed, a set of issues involving engineering, regulation, security, and social frameworks have been derived in a theoretical fashion. The findings are likely to suggest the urgent need for multidisciplinary cooperation to address engineering and ontological challenges gravitating around the smart grid concept.